Advancing educational robotics: competence development for pre-service computer science teachers - Nataliia V. Morze; Oksana V. Strutynska (Academy of Cognitive and Natural Sciences, 2023)
The rapid growth of robotics as an applied industry has created a pressing demand for robotics specialists skilled in the development, design, and programming of robots. This has led to the widespread popularity of robotics as an educational trend, both in Ukraine and worldwide. Integrating educational robotics into STEAM education offers a powerful platform for cultivating students' soft skills, enabling them to tackle real-world socially significant projects and bridging the gap between theoretical knowledge and practical application. Consequently, there is a crucial need to equip pre-service teachers with the necessary skills to effectively teach educational robotics to students. This article addresses the issue of establishing a comprehensive model of competences in educational robotics for teachers and explores strategies for their development. The research demonstrates that pre-service computer science teachers exhibit the highest readiness to teach educational robotics in secondary schools. The article focuses on developing and validating a model of competences in educational robotics for pre-service computer science teachers, highlighting its effectiveness through the teaching of educational robotics disciplines. By fostering competence development among teachers, this study aims to advance the integration of educational robotics in classrooms, empowering students to thrive in a digitally-driven society.